Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas II SD IT Bina Ilmi Lemabang Dengan Menggunakan Media Papan Perkalian - Desi Ratnasari; Didi Suhendi (Algebra: Journal of Matematics, Statistics and Computation, 2024)
The research aims to improve the mathematics learning outcomes of class II students at SD IT Bina Ilmi Lemabang by using multiplication board media. This type of research is Classroom Action Research. The research subjects were 26 grade II students at SD IT Bina Ilmi Lemabang. This research was conducted in 2 cycles. Data collection was carried out by observation and tests. Data analysis was carried out descriptively. The research results showed that there was an increase in the average value of the pre-cycle, cycle I and cycle II. In the pre-cycle practice, there were 5 students or 23.09% who passed the KKM and with an average of 59 in Mathematics. In the first cycle remedial practice, there were 18 students or 69.22% who passed the KKM and with an average Mathematics 79. Meanwhile, in the second cycle of practice, there were 24 students or 92.31% who passed the KKM and with an average of Mathematics 89. It can be concluded that the use of multiplication board media can improve the mathematics learning outcomes of class II students at SD IT Bina Ilmi.